2020
DOI: 10.3389/fenvs.2019.00202
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter Is a Mixture of Terrestrial, Autochthonous, and Wastewater Effluent in an Urban River

Abstract: Terrestrially derived organic matter (OM) is known to dominate the OM pool in reference watersheds. Urban watersheds are known to receive large OM loads compared to reference watersheds, but the proportion of terrestrial, autochthonous, and anthropogenic (e.g., wastewater effluent) sources of OM in urban watersheds remains unknown. Organic matter was identified as a pollutant of concern in the Jordan River, an urban river in the Salt Lake Basin, U.S.A. Our objective was to identify autochthonous, terrestrial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Agriculture depletes soil OM (McLauchlan, 2006) and increases both allochthonous OM inputs and DOM lability in aquatic ecosystems (Shang et al., 2018; Stanley et al., 2012). Urbanization also increases DOM lability in surface waters due to increased wastewater inputs and autochthonous production (Kelso & Baker, 2020; Z. Wu et al., 2019; Hosen et al., 2014). Both urbanization and agricultural intensification increase NO 3 − loads in runoff from fertilizer application, human and animal waste, and atmospheric deposition (Jordan & Weller, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture depletes soil OM (McLauchlan, 2006) and increases both allochthonous OM inputs and DOM lability in aquatic ecosystems (Shang et al., 2018; Stanley et al., 2012). Urbanization also increases DOM lability in surface waters due to increased wastewater inputs and autochthonous production (Kelso & Baker, 2020; Z. Wu et al., 2019; Hosen et al., 2014). Both urbanization and agricultural intensification increase NO 3 − loads in runoff from fertilizer application, human and animal waste, and atmospheric deposition (Jordan & Weller, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This idea is supported by the low C:N ratios measured at the Cànoves stream (from 12:1 to 15:1), which are substantially lower than those reported for total organic matter in rivers worldwide (from 30:1 to 60:1) (Bauer et al, 2013). In urban streams, FPOM is usually a mixture of terrestrial, autochthonous and wastewater effluent sources, the latter source contributing >50% when hydrological dilution is low (Kelso and Baker, 2020). Therefore, and given that the study reaches were downstream of a WWTP effluent, we propose that this was an important source of FPOM in the Cànoves stream.…”
Section: Quality and Not Quantity Of Streambed Fpm Influences Metabolic Activitymentioning
confidence: 88%
“…The organic fraction of the FPM (i.e., fine particulate organic matter, FPOM) can consist of fecal particles from shredder invertebrates as well as fragments of organic particles generated both in streams and adjacent soils (Bundschuh and McKie, 2015). Stream FPOM can also derive from anthrogenic point sources such as wastewater treatment plant (WWTP) effluents which usually act as important sources of particles, dissolved organic carbon and nutrients (Marti et al, 2004;Merbt et al, 2014;Bernal et al, 2020;Kelso and Baker, 2020). Although FPOM can be highly processed organic matter; and therefore, expected to be a more recalcitrant OM source than the dissolved organic fraction, FPOM can act both as a colonizing surface for microorganisms and as a carbon source for microbial activity within streams (Hope et al, 1994;Brugger et al, 2001;Gottselig et al, 2014) and eventually can be more labile than dissolved organic matter (Stutter et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that elevated indicators of autochthonous production increased the proportion of bioavailable DOM and were related to sources of anthropogenic waste signified SMITH ET AL. by tryptophan-like fluorescence (Kelso & Baker, 2020;Osburn et al, 2012; Figure 6). Interestingly, elevated heterotrophic BA and activities during the wet season, when the water table is high, led to shifts in microbial utilization of C from allochthonous sources to autochthonous sources.…”
Section: Discussionmentioning
confidence: 99%
“…In coastal drainages, DOM originates from a range of allochthonous and autochthonous sources including terrestrial plants and soil, bacterial or algal production contributions, and exudates from marine phytoplankton (Asmala et al., 2016; Romera‐Castillo et al., 2010; Sobczak et al., 2002). The role of DOM in biogeochemical cycling is a function of its composition (i.e., quality) and is driven by changes in land use (Kaushal & Belt, 2012; Kelso & Baker, 2020; Kominoski & Rosemond, 2012; Wilson & Xenopoulos, 2009) and hydrologic conditions, such as stormwater runoff and tidal mixing (Duan et al., 2014; Gardner, et al., 2005; Hosen et al., 2014). Despite the abundance of DOM in aquatic ecosystems, often only a small fraction is bioavailable (i.e., easily degradable; Parr et al., 2015).…”
Section: Introductionmentioning
confidence: 99%